Predicting social tipping points: current research and the way forward - Sonja Grimm; Gerald Schneider (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The prediction of the breakdown of social order is both a considerable academic challenge and a major development concern. This essay argues that the three main approaches used to assess these risks – the structural , the dynamic and the game-theoretic approaches – supplement each other in the task of predicting extreme events. Although these approaches – alone or in conjunction with each other – can help to identify some real risks, one of the key problems is the translation of these findings into reasonable policy recommendations. One particular challenge that the academic world and practitioners have to address is the forecasted effectiveness of various policies that aim at reducing the risk of social and political instability.
Keywords: 330